Pelatihan Komunikasi Interpersonal Untuk Meningkatkan Kohesivitas Kelompok Pada Karyawan Hotel X Yogyakarta - Didik Widiantoro; Sukarti Sukarti; Sus Budiharto (JIP (Jurnal Intervensi Psikologi), 2017)
This research is aiming for influence of interpersonal communication training to improve the cohesiveness of the group of employees. Subjects in this study were 22 employees of Hotel X of Yogyakarta, which is divided into 11 experimental groups of employees and 11 employees of the control group. Data collection is use cohesiveness scale, interviews, and observations. The research design was pretest-posttest control group design. Analysis of the study is a quantitative and qualitative analysis. Quantitative analysis using U-Mann Whitney to determine the effect of interpersonal communication training to the employee group cohesiveness. Qualitative analysis is based on observations and interviews. The results showed that there were significant differences in group cohesiveness in employees between the experimental group and the control group with significant value of 0.002 (p <0.005). It is concluded that interpersonal communicationtraining can enhance group cohesiveness in employees Hotel X Yogyakarta.Keywords: Interpersonal Communication Training, Cohesiveness group, Employee